A new giant anole (Squamata: Iguanidae: Dactyloinae) from southwestern Ecuador - Ayala-Varela, Fernando; Valverde, Sebastián; Poe, Steven; Narváez, Andrea E.; Yánez-Muñoz, Mario H.; Torres-Carvajal, Omar (Zootaxa, 2021)
We describe a new species of Anolis lizard from the Pacific slopes of the Andes of southwestern Ecuador at elevations between 372–1,000 m. The new species belongs to the Dactyloa clade and may be distinguished from other Anolis by size, external anatomy, mitochondrial DNA divergence, and dewlap color. Based on phylogenetic analyses of mitochondrial and nuclear DNA sequence data, we found that the new species is sister to A. fraseri in a clade composed primarily of large Dactyloid species. The new species is known from a protected area in southern Ecuador, Buenaventura Reserve, which suggests that at least some its populations are well protected.